Strategi Peningkatan Layanan Mobile Banking BTN Syariah Meulaboh Berdasarkan Analisis Kesenjangan (Gap Analysis) - Basuki, Mahmud; Irawan, Risnadi; Nuzuli, Fajar; Irawan, Heri Tri; Syahputra, Riski Agam; Azhar, Azhar (Universitas Teuku Umar, 2025)
Every company competes by developing strategies to outperform its rivals in the same market, whether through variations in the products offered, promised facilities, or the quality of services delivered to customers. BTN Syariah KCPS Meulaboh, located in Ujong Baroh Village, Johan Pahlawan District, West Aceh Regency, is a branch office of PT Bank Tabungan Negara (BTN). One of the recurring issues at this branch is related to the services provided through Mobile Banking (M-Banking). This study aims to identify the key attributes used to measure service quality and to determine the level of customer satisfaction regarding M-Banking services at BTN Syariah KCPS Meulaboh. Based on the results of research using the Improvement Gap Analysis (IGA) method, it was found that there are 12 attributes across 3 dimensions used to evaluate service quality. The overall findings indicate that customer satisfaction with the performance of Mobile Banking services at BTN Syariah KCPS Meulaboh is low, as reflected in the average questionnaire results showing dissatisfaction with the current M-Banking performance.